SINERGI KURIKULUM NASIONAL DAN PESANTREN; PENGEMBANGAN PENDIDIKAN BAHASA ASING DI MI MAMBAUL ULUM BATA-BATA PAMEKASAN - Ridho, Muhammad Izul; Basit, Abdul; Suhri, Ahmad (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Curriculum renewal is an important step in improving the quality of education. Integration of the national curriculum and Islamic boarding schools can have a positive impact on the development of foreign language education. This study aims to analyze how curriculum renewal is carried out at MI Mambaul Ulum Bata-Bata Pamekasan. In addition, this study also aims to determine the form of synergy between the national curriculum and Islamic boarding schools in foreign language education at MI Mambaul Ulum Bata-Bata Pamekasan. The research method used is a qualitative descriptive method with a case study approach. The results of the study indicate that curriculum renewal at MI Mambaul Ulum Bata-Bata is carried out by adopting the national curriculum and integrating it with Islamic boarding school values. The synergy between the national curriculum and Islamic boarding schools is manifested in the form of foreign language learning that not only focuses on language skills, but also on understanding religious and cultural values. The implementation of this curriculum is also supported by competent teaching staff and adequate facilities. However, this study has not examined the impact of curriculum implementation on students' foreign language skills comprehensively, so further research is needed to measure the effectiveness of this curriculum.